2019
DOI: 10.1049/iet-wss.2018.5049
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of wireless MEMS sensor network for detection of gait events

Abstract: MEMS based wireless sensor network (WSN) for real-time human health monitoring is promising in home-based rehabilitation. It requires effective integration of a number of MEMS sensors and their placement on the human body to create a wireless body area network for continuous and timely monitoring of various biophysical parameters. This study attempts to develop an XBee-based WSN for real-time monitoring of human gait. Traditionally, the optical motion systems were used for gait analysis but they suffer from ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Continuous advancements in MEMS sensor technology provide the opportunity to integrate the low-power WSN with a wireless communication protocol for long-term, continuous, and real-time monitoring [76]. However, for terrestrial applications, the development of MEMS sensor technology, wireless communications, embedded systems, distributed processing, and wireless sensor applications have a major transition in the wireless sensor network for marine environmental monitoring.…”
Section: Role Of Mems Sensor Technology With Wireless Communication I...mentioning
confidence: 99%
“…Continuous advancements in MEMS sensor technology provide the opportunity to integrate the low-power WSN with a wireless communication protocol for long-term, continuous, and real-time monitoring [76]. However, for terrestrial applications, the development of MEMS sensor technology, wireless communications, embedded systems, distributed processing, and wireless sensor applications have a major transition in the wireless sensor network for marine environmental monitoring.…”
Section: Role Of Mems Sensor Technology With Wireless Communication I...mentioning
confidence: 99%
“…In the research, each sensor node is developed from an arduino based microcontroller and Xbee wireless module based on Zigbee/IEEE 802.15.4 standards. The study found an increase in baud rate also increases throughput and decreases packet delay in line of sight (LOS) condition [17] [18]. Whereas in comparison of the performance of multihop communication networks and direct communication shows that the performance of multi-hop networks has decreased compared to direct transmission in terms of data throughput and packet delay [19]…”
Section: Introductionmentioning
confidence: 97%
“…Several technologies, like digital electronics and MEMS and communication, 9 are more advanced, which have created the space for the development of different types of sensors with low cost and lightweight nodes for the WSNs. Advancements in the micro‐electro‐mechanical systems and wireless communications have eased the development of low‐power and low‐cost sensor nodes for monitoring the sensing environment with vital parameters like temperature, humidity, etc.…”
Section: Introductionmentioning
confidence: 99%